Remote web-based cat food dispenser (DiCatDiHati) / Ahmad Faizwan Azmi and Mohammad Hafiz Ismail - Azmi, Ahmad Faizwan; Ismail, Mohammad Hafiz (UiTM Cawangan Perlis, 2017)
The Remote Web-based cat food dispenser is a design that will help the cat owners to monitor or to feed their cats even without their presence. Currently, most of the cat owner feed their cats manually and sometimes they forgot to feed their cats before leaving home. This attitude can lead their cats for having unbalanced "diet" because beside did not feed their cat, the food that they fill in on the eating plate early in the morning also will be unhealthy. That food will expose to the air and it is not fresh anymore to be eat. The objective of this project are to identify the requirement in building and develop Remote Web-based Cat Food Dispenser that interfaces both smartphone and computer. Remote Web-based Cat Food Dispenser may have multiple function like the cat owners can feed their cats, check the balance of food in the container and set a notification or alarm for them. The waterfall model concept was been used for the software development model. The waterfall model contains some consecutives phases where each phases must be completed before moving to next phase (Bassil, 2012). Two type of testing has been conducted to accomplish the third objective of this project which are User Acceptance Test and Usability Test. Most of the cat owner give high marks on the User Acceptance. This concludes that Remote Web-based Cat Food Dispenser can be implemented by the cat owners in order to help their cat having a balance diet.